Magneto-thermoelectric Effects in Cylindrical Quantum Wire under the Influence of Electromagnetic Wave for Electron-optical Phonon Scattering - Hung, Tran Hai; Quang Bau, Nguyen; Minh Quang, Doan (VNU Journal of Science: Mathematics - Physics; Vol 35 No 4DO - 10.25073/2588-1124/vnumap.4400, 2019)
This paper studies the influence of a strong electromagnetic wave (EMW) on the magneto-thermoelectric effects in a cylindrical quantum wire with an infinite potential (CQWIP) (for electron - optical phonon scattering) under the influence of electric field , magnetic field  and a strong EMW (laser radiation)  (where  and  are amplitude and frequency of EMW, respectively), based on the quantum kinetic equation for electrons. The study obtained the analytic expressions for the kinetic tensors  and the Ettingshausen coefficient (EC) in the CQWIP with the dependence on the frequency, the amplitude of EMW, the Quantum Wire (CQWIP) parameters, the magnetic field and the temperature.  The study results were numerically evaluated and graphed for GaAs/GaAsAl quantum wire. Then, the results in this case were compared with those in the case of the bulk semiconductors and other low-dimension systems in order to show the difference and the novelty of the current results. Moreover, it is realized that as the EMW frequency increases, the EC fluctuates with a stable trend, and the appearance of the Shubnikov-de Haas (SdH) oscillations pattern when the dependence of EC on the magnetic field is surveyed.